Apixaban Suppresses the Release of TF-Positive Microvesicles and Restrains Cancer Cell Proliferation through Directly Inhibiting TF-fVIIa Activity - Featherby, Sophie; Madkhali, Yahya; Maraveyas, Anthony; Ettelaie, Camille (Thrombosis and Haemostasis, 2019)
The activation of protease-activated receptor (PAR)-2 by factor Xa (fXa) promotes the release of tissue factor-positive microvesicles (TF+MV), and contributes to proliferation in cancer cells. This study examined the ability of direct oral anticoagulants (DOACs), apixaban and rivaroxaban, to inhibit the release of TF+MV from two cell lines (MDA-MB-231 and AsPC-1) as well as cell proliferation.Activation of the cells with fXa (10 nM) enhanced the release of TF+MV but was suppressed in the presence of either DOAC. These MVs were found to contain fVIIa, but not fXa. Incubation of cell lines with apixaban (1.8 µM) but not rivaroxaban (1.8 µM), in the absence of fXa decreased the release of TF+MV below that of resting cells, in a PAR2-dependent manner. Furthermore, incubation with apixaban reduced the proliferation rate in both cells lines. Incubation of purified fVIIa with apixaban but not rivaroxaban resulted in complete inhibition of fVIIa proteolytic activity as measured using two fVIIa chromogenic substrates. Pre-incubation of the cells with an inhibitory anti-fVIIa antibody, with apixaban or the blocking of PAR2 suppressed the release of TF+MV to a comparable level, and reduced cell proliferation but the effect was not cumulative.This study has established that the activation of PAR2 by TF–fVIIa complex is the principal mediator in augmenting the release of TF+MV as well as cancer cell proliferation. Importantly, for the first time we have shown that apixaban selectively inhibits the proteolytic activity of fVIIa as well as the signalling arising from the TF–fVIIa complex.
Keywords: direct oral anticoagulants; factor VIIa; microvesicles; protease-activated receptor-2; tissue factor